Java Software Solutions: Foundations of Program Design - Lewis, John, 1963-; Loftus, William (USA Addison Wesley Longman, Inc., 1998)
Using Java(TM) 1.1, Java Software Solutions teaches beginning programmers how to design and implement high-quality object-oriented software. The authors emphasize problem solving through understanding requirements, exploring options, and designing conceptually clean solutions. John Lewis and Bill Loftus wrote this book from the ground up, taking full advantage of Java to teach introductory programming. Throughout the book, the authors intertwine the use of applets and applications to demonstrate computing concepts. Applets are introduced early, building on the excitement of the web, while applications are used for readers to gain a clear understanding of programming concepts.
Donated by: Anvar Hodjaev
Keywords: Java; Computer Science